Contribution of PCR Denaturing Gradient Gel Electrophoresis Combined with Mixed Chromatogram Software Separation for Complex Urinary Sample Analysis - Kotásková, Iva; Mališová, Barbora; Obručová, Hana; Holá, Veronika; Peroutková, Tereza; Růžička, Filip; Freiberger, Tomáš (Journal of molecular microbiology and biotechnology, 2017)
Complex samples are a challenge for sequencing-based broad-range diagnostics. We analysed 19 urinary catheter, ureteral Double-J catheter, and urine samples using 3 methodological approaches. Out of the total 84 operational taxonomic units, 37, 61, and 88% were identified by culture, PCR-DGGE-SS (PCR denaturing gradient gel electrophoresis followed by Sanger sequencing), and PCR-DGGE-RM (PCR- DGGE combined with software chromatogram separation by RipSeq Mixed tool), respectively. The latter approach was shown to be an efficient tool to complement culture in complex sample assessment.
Keywords: Urine; Mixed chromatogram; DNA, Bacterial; Molecular Diagnostic Techniques; Bacteria; Urinary Catheters; denaturační gradientová gelová elektroforéza; polymerázová řetězová reakce; Polymerase Chain Reaction; RipSeq Mixed; DNA bakterií; moč; močové katétry; Humans; Software; PCR denaturing gradient gel electrophoresis; Diagnostic Techniques, Urological; Complex sample; software; diagnostické techniky molekulární; diagnostické techniky urologické; Catheter; Denaturing Gradient Gel Electrophoresis; lidé